Diverse developmental programs of Xenopus laevis metamorphosis are inhibited by a dominant negative thyroid hormone receptor - Schreiber, Alexander M. (The National Academy of Sciences, 2001)
Metamorphosis of anuran tadpoles is controlled by thyroid hormone (TH). Here we demonstrate that transgenic Xenopus laevis tadpoles expressing a dominant negative form of TH receptor-α are resistant to a wide variety of the metamorphic changes induced by TH. This result confirms that TH receptors mediate both early and late developmental programs of metamorphosis as diverse as growth in the brain, limb buds, nose and Meckel's cartilage, remodeling of the intestine, and death and resorption of the gills and tail.